博多湾におけるマクロベントスを考慮した水質解析 - KUMAGAI Hiroshi; YAMASAKI Koreyoshi; WATANABE Ryoichi; FUJITA Kenichi (ENVIRONMENTAL ENGINEERING RESEARCH, 2004)
In this study we present a new ecosystem model which has a compartment of a macrobenthos Muscalista senhousia which was mainly dominated in sediment at shallow water area of Hakata Bay. The results of water qualities estimated by this newly developed model were more precise than that estimated by a model which does not have the macrobenthos compartment. This result shows that macrobenthos in the sediment has a great effect on estimating the water concentrations and forecasting the behavior of oxygen-deficient water body.